An Approach for Performance Assessment of Tracked Vehicle Transmission Based on the Median-Rank Weight and the Least-Square Support Vector Machine. (20th July 2022) - Zou, Tiangang; Zhang, Jinbao; Yan, Qingdong; Wei, Ran; An, Yuanyuan
Abstract : Transmission efficiency is one of the important indicators for the performance assessment of the tracked vehicle transmission device. Considering the influence of many factors in the transmission process at the straight driving mode, an approach for constructing the normalized comprehensive performance assessment indicator is proposed based on the median rank of no-load power loss and the median rank of transmission efficiency. Then, the performance assessment of the single tracked vehicle transmission device is performed with the least-square support vector machine (LSSVM). The results show that the stable comprehensive performance assessment indicator could be obtained in the first 10 speed measurement points, and the performance state of the vehicle transmission device is identified according to the criterion.